Digital Economy in Czech Republik, Slovakia and Hungary. Measurement with Topsis based on Entropy Measure for Objective Weighting - Adam P. Balcerzak (Institute of Economic Research (IER), 2017)
Effective digital economy is currently considered as a factor that can increase chances for avoiding middle income trap in Central European economies. Taking into account regional perspective building conditions for developing digital economy can support the process of closing development gap and utilizing the potential of convergence in the case of underdeveloped or peripheral regions. As a result, supporting the digital economy is currently considered as an important policy objective both form national and regional perspective. Thus, the objective of the article is to compare the development level of the digital economy in Czech Republic, Slovak and Hungary. The research was conducted for the year 2015. In the research the digital economy is defined as a multiple-criteria phenomenon, which is described with diagnostic variables proposed by Eurostat for measurement of the digital economy at regional level (NUTS 1). In the article TOPSIS method was implemented. In the case of every multiple-criteria analysis tasks a basic dilemma relates to the problem of applying weights for variables used in the research, which should be appropriate for their importance in forming the measured phenomenon. To solve that problem two approaches were applied here. First, the TOSPIS method with equal weights for all the variables was used. In the second approach the TOPSIS method was extended with Shannon entropy and objective weights concept. The obtained results confirm some disparities between the regions in the analyzed part of Central Europe and the importance of habits and human capital in the process of utilizing potential of the digital economy.
Keywords: P25; C38; 330; digital economy; multiple-criteria decision analysis (MCDA); TOPSIS; Shannon entropy; objective weights